X-ray tomographic data of planktonic foraminifera species Globigerina bulloides from the Eastern Tropical Atlantic across Termination II - Stergios D. Zarkogiannis (GigaScience Press, 2020)
Increased planktonic foraminifera shell weights were recorded during the course of Termination II at a tropical site off the shore of the Mauritanian coast. In order to investigate these increased shell mass values, a series of physicochemical analyses were performed, including X-ray computed tomography (CT). The data are given here. Furthermore, the relevant CT setup, scanning, reconstruction, and visualization methods are explained and the acquired datasets are given, together with 3D volumes and models of the scanned specimens.